A contribuição das universidades de massa para a promoção da mobilidade socioeconômica e cultural de seus concluintes - Parenti, Ana Flávia da Costa (2017)
This work looks to investigate and analyse how much private Universities, hereafter designated as mass and profit-oriented Universities, can contribute for rising social, economic and cultural useful capital for its students. To do that, it´s been discussed the importance of those Universities for the National Education efforts, the evolution of the Brazilian Policies in this branch, the impact of the privatization process in the sector, and the influence of international financial groups migrating to this economic activity, by making acquisitions of Faculties and Universities, turning them into great organizations, precarianess Education by assuming a profit-oriented logic. The empirical data were based on surveys taked with students attending to the Course of Business Administration of an important private University in the East of São Paulo city. This course was chosen because it has the biggest number of students enrolled. It´s been picked up students at the beggining and at the end of the course. Teachers were also surveyed in search for informations about work conditions and the relationship with students in classroom